Simultaneous Determinants of Market Share and Advertising Expenditure under Dynamic Conditions: The Case of a Firm within the Japanese Pharmaceutical Industry - Hiroki Tsurumi; Yoshi Tsurumi (Queen's University, Department of Economics, 1971)
The main objective of this model is to analyse the simultaneous determination of market share and advertising expenditure under dynamic conditions. The authors' empirical analysis is applied to the case of the Eisai Company within the Japanese pharmaceutical industry from 1959 to 1969. Although the model is limited to this particular company and industry, the theoretical formulations and estimation techniques together with the particular distributed lag used may be usefully applied to other cases.
Keywords: 330